Development and Initial Validation of a Life Event Scale for Students - Linden, Wolfgang (Canadian Journal of Counselling and Psychotherapy, 2011)
The present study represents a readaptation of the Social Readjustment RatingScale for college and university students. Student-typical items were empiricallyderived and normative data on each item were collected from a sample of 176students. An initial attempt to validate this new scale indicated significantly higherfrequencies of medical illness, seeking of psychological help, and academic failuresin individuals with above average life change.